1989
DOI: 10.1111/j.1365-2958.1989.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the osmoregulated Escherichia coli proU promoter and identification of ProV as a membrane‐associated protein

Abstract: The Escherichia coli proU operon encodes a high-affinity, binding-protein-dependent transport system for the osmoprotectant glycine betaine. Expression of proU is osmoregulated, and transcription of this operon is greatly increased in cells grown at high osmolarity. Characterization of the proU operon and its promoter provided results similar to those published elsewhere (Gowrishankar, 1989; Stirling et al., 1989). The previously identified proU601 mutation, which leads to increased proU expression both at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 45 publications
1
45
0
1
Order By: Relevance
“…We have previously reported that multicopy plasmids carrying the proU601 mutation in a FD(proV-lacZ)(Hyb2) fusion plasmid rapidly acquire secondary mutations that strongly decrease the expression of the fusion (31 (33). When these clones were sequenced, a variety of mutations in the proU promoter were recovered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that multicopy plasmids carrying the proU601 mutation in a FD(proV-lacZ)(Hyb2) fusion plasmid rapidly acquire secondary mutations that strongly decrease the expression of the fusion (31 (33). When these clones were sequenced, a variety of mutations in the proU promoter were recovered.…”
Section: Methodsmentioning
confidence: 99%
“…No classical regulatory protein has been identified for proU. Mutants with increased proU expression carry either cis-acting mutations closely linked to proU (12,23,31) or trans-acting mutations in topA or osmZ (23). The products of these genes, DNA topoisomerase I and the histonelike DNAbinding protein H-NS (Hla), respectively, are known to affect DNA topology, and mutations in these genes increase moters; however, the proU -10 region deviates from the consensus (TATAAT) sequence at three positions (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…coli can synthesize the compatible solute trehalose de novo and can convert choline to glycine betaine. If provided with the medium, E. coli is able to transport and amass a variety of different compatible solutes, such as ectoine, proline and glycine betaine, with the help of the transporters ProP and ProU (Milner et al, 1988;May et al, 1989). In order to feed myxobacteria without contaminating compatible solutes, we designed the trehalose-free E. coli strain BKA-13, which is based on E. coli MHK-13 (Haardt et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Chez E. coli, l'ABC transporteur ProU est localisé au niveau de l'enveloppe et est composé de 3 protéines : une protéine cytoplasmique d'hydrolyse de l'ATP (ATPase ou ATPbinding cassette, ProV), caractéristique des ABC transporteurs, qui fournit l'énergie au système, une protéine membranaire (ou perméase, ProW) servant au passage de la glycine bétaïne vers le milieu interne et un polypeptide périplasmique hydrophile de liaison au substrat (ProX). La perméase ProW est constituée de 6 domaines transmembranaires aux extrémités carboxy-et amino-terminale cytoplasmiques et semble fonctionner comme un homodimère avec l'ATPase ProV [1,23]. Chez L. lactis, l'étude de la séquence de l'opéron opuA indique que ce système appartient à la superfamille des ABC transporteurs.…”
Section: Réponse Physiologiqueunclassified